Bidirectional Interaction of Thyroid-Kidney Organs in Disease States - Fateme Shamekhi Amiri (International Journal of Nephrology)
Purpose. Thyroid hormones play an important role in growth, development, and physiology of the kidney. The kidney plays a key role in the metabolism, degradation, and excretion of thyroid hormones and its metabolites. The aim of this study is to investigate the prevalence of disease states of thyroid-kidney organs and detecting the correlation between thyroid and kidney function abnormalities. Materials and Methods. In this retrospective study, a total of forty-five patients with thyroid and kidney dysfunction were investigated. Clinical features, laboratory data at initial presentation, management, and outcomes were collected. The paper has been written based on searching PubMed and Google Scholar to identify potentially relevant articles or abstracts. Median, percentage, mean ± standard deviation (SD), and the two-tailed t-test were used for statistical analyses. The correlation between variables was assessed by Pearson’s, Spearman’s correlation tests and regression analyses. Results. The mean ± SD of age of study patients was 48.2 ± 22.93 years (ranging from 1 to 90 years). There was no correlation between serum thyroid-stimulating hormone, free thyroxine levels with estimated glomerular filtration rate, and proteinuria. No association between antimicrosomal antibodies with estimated glomerular filtration rate was seen. Cardiovascular disease was the most common complication of overt hypothyroidism in kidney dysfunction patients. Conclusion. The present study showed more prevalence of primary hypothyroidism in comparison with other thyroid dysfunctions in patients with kidney dysfunction. Reduced mean values of thyroid function profiles after treatment suggest that this thyroid disease should be considered and ameliorated with thyroid hormone replacement therapy in patients with kidney disease.